Iʿjāz of the Qurʿān for Using the Words Gold, Silver and Not Money - Belabes, Abderrazak (Universitas Muhammadiyah Surakarta, 2024)
The production of knowledge on iʿjāz in economy is strongly influenced by the literature on scientific miracles of the Qurʿān. The interpretation of the verses of the Qurʿān pertaining to maʿāsh comes up against the binary logic aimed at constructing a scientific identity by summoning key concepts from mainstream economic thought. This article is based on philology as an art of reading well to shed light on the iʿjāz of the Qurʿān through the use of the words gold and silver and not that of money. It is structured around multidisciplinary approach and a qualitative analysis through the meanings in reference to the literature on the secrets of eloquence and evidence of the inimitability of the Qurʿān. The results showed that the iʿjāz in the use of the words gold and silver invites to live in the world of rizq, as an umwelt or 風土 fūdo. This mode of existence provides resilience against voluntary servitude to the system of monetary creation ex nihilo by the interest loan granted by commercial banks. Such particular way is a thematic interpretation of the verses relating to the means to acquit the rights of the Creator and those of the creatures. It converges like Hénon attractor as a chaotic fractal set with research in history, anthropology and numismatics which does not use the word money.